2021
DOI: 10.1002/joc.7363
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the sensible heat of rainfall in the tropics from reanalysis and observations

Abstract: Precipitation cools the surface because the temperature of raindrops is typically lower than the temperature of the surface. This precipitation‐induced sensible heat flux (QP) due to the temperature difference between the surface and raindrops is thought to be small and is typically ignored in weather and climate models. However, there are many instances in which instantaneous values in QP can be large, especially in extreme rainfall events. In this study, we provide a systematic estimate of QP over the tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…For example, Gosnell et al (1995) found that Q P in the tropical warm pool area can reach up to 200 W m 2 . As a result, Q P may significantly affect the regional climate, especially during heavy rain events (e.g., Anderson et al, 1998;Boike et al, 2003;Gillett & Cullen, 2011;Gosnell et al, 1995;Ramos et al, 2022;Wei et al, 2014). A detailed review of past studies related to Q P can be found in Ramos et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gosnell et al (1995) found that Q P in the tropical warm pool area can reach up to 200 W m 2 . As a result, Q P may significantly affect the regional climate, especially during heavy rain events (e.g., Anderson et al, 1998;Boike et al, 2003;Gillett & Cullen, 2011;Gosnell et al, 1995;Ramos et al, 2022;Wei et al, 2014). A detailed review of past studies related to Q P can be found in Ramos et al (2022).…”
Section: Introductionmentioning
confidence: 99%